A study of the workload and effectiveness of a comprehensive acute stroke service. - Weir, N; Buchan, A (2005)
OBJECTIVE: To study the workload of and use of acute intervention within an established acute stroke service, the Calgary Stroke Programme (CSP). METHODS: Prospective record of all acute referrals, diagnoses, and management decisions over a 4 month period. RESULTS: The CSP received 572 referrals (median: 32 per week), 88% of which were made between 7 am and midnight. Of the 427 patients seen in person, 29% had not had an acute stroke or transient ischaemic attack (TIA). Fifty percent of patients with suspected acute stroke were referred within 3 h of symptom onset and 11% with acute ischaemic stroke (equating to 35% of those referred within 3 h of onset and seen in person) were treated with thrombolysis. CONCLUSION: Centralisation of services facilitates the rapid referral of, and use of acute interventions in, patients with acute stroke and TIA. Centralised services are likely to be busy (although less so at night), to attract large numbers of patients with disorders that mimic stroke and TIA, and yet still likely to treat only the minority of acute strokes using thrombolysis. These observations may help those planning similar services and underline the need to develop more widely applicable treatments for acute stroke.